The identity of female cyborg in William Gibsons Neuromancer - Yap, Geraldine Chee Hui; Babaee, Ruzbeh (Australian International Academic Centre, Australia, 2015)
This study aims to examine the identity of female cyborg in William Gibson’s Neuromancer (1984) based on Donna Haraway’s A Cyborg Manifesto. In Neuromancer the main character, Molly Million does not fit in the stereotypical female characteristics. When a male is the protagonist, females will be seen as a feminine stereotype and being depicted as helpless and weak. She is in fact the reversal of feminine stereotype. Henry Dorsett Case, the male protagonist of the story, was given a job opportunity and being partnered up with Molly to fulfil their mission. When Molly and Case are together, Case is always on the safe side while Molly aggressively moves around getting her things done. Being a cyborg is to be fierce, fast and bold just like Molly and being a goddess will be a typical female. It is a metaphor used to conceptualize socialist feminism in the modern society. The boundary breakdown between organism and machine portrays the boundary breakdown between Molly and Wintermute, an Artificial Intelligence (AI), because Molly and Wintermute are representatives of organism and machine, respectively. When Molly and Wintermute could put up with each other, it indirectly shows the connection between human and technology that can then be brought to another level as dualism of mind and body that are considered as one in the cybernetic world just like how high technology and scientific culture are interrelated. Mind which symbolizes Artificial Intelligence is the ultimate power which controls the body. The technological enhancements in Molly are the symbolised power which gives her the difference in stereotypical female role.